2014
DOI: 10.1177/1746197914520652
|View full text |Cite
|
Sign up to set email alerts
|

Students’ understandings of religious identities and relations: Issues of social cohesion and citizenship

Abstract: The focus in this article is on issues of social cohesion and citizenship as they relate to students' understandings of religion and religious identity. The article draws on data gathered from a study conducted at a highly diverse English comprehensive school and is set amid broader anxieties about religion, community disharmony and national identity in the United Kingdom. The high levels of religious diversity at the school were seen as supporting social cohesion -enabled in this context through students' und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
0
6
0
1
Order By: Relevance
“…The ability of minority pupils to participate in these Christian celebrations often depends on whether they are perceived as religious or cultural, such as if they are held in a church or school hall (Wilson 2015). Many schools also choose to mark minority religious festivals such as Eid, Diwali, Hanukkah and Vaisakhi (Keddie 2014, Nesbitt 2004. It is widely viewed as appropriate to recognise non-Christian festivals in an educational sense, during assemblies or classroom discussions (e.g.…”
Section: Recognition: Religious Education and Festivalsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of minority pupils to participate in these Christian celebrations often depends on whether they are perceived as religious or cultural, such as if they are held in a church or school hall (Wilson 2015). Many schools also choose to mark minority religious festivals such as Eid, Diwali, Hanukkah and Vaisakhi (Keddie 2014, Nesbitt 2004. It is widely viewed as appropriate to recognise non-Christian festivals in an educational sense, during assemblies or classroom discussions (e.g.…”
Section: Recognition: Religious Education and Festivalsmentioning
confidence: 99%
“…There are variations in the extent to which schools in England and Wales explicitly recognise diversity of religion and belief, but most appear to encourage a climate of tolerance and respect for difference (e.g. Keddie 2014, Hemming 2015. There is also plenty of evidence in the research literature to suggest that schools with a religious character actively educate pupils to respect religious difference (Ipgrave 2016, Wilson 2015.…”
Section: Belonging: Pupil Values and Interfaith Relationsmentioning
confidence: 99%
“…Task-based interviews with 116 students in Colombia, Northern Ireland, the Republic of Ireland and the United States demonstrated participants' awareness of global, national, and local human rights issues, and the differential salience of these issues to various students depending on national discursive contexts, school instruction, and personal experience (Barton, 2015). Discussion-based inquiry with ten students in one integrated, justice-oriented English high school (Keddie, 2014) showed that participating young people were well aware of inter-religious conflicts and biases in their society, but they viewed religious identities as socially constructed and contingent, and considered themselves to be supportive of religious diversity. Another exploratory study, in Ontario, Canada, showed that participating high school students were emotionally affected by events surrounding the September 2001 terrorist attacks on the USA, and that they had developed some historical understanding of the social conflict roots of terrorism (Levesque, 2003).…”
Section: Young People's Understandings Of Social Conflict and The Potmentioning
confidence: 99%
“…Hemming (2015) found that primary school practices were important for the fostering of positive relations between pupils of different faiths, through the teaching of 'emotion work' and other embodied forms of social cohesion. Keddie (2014) similarly recognised the importance of school ethos for harmonious inter-faith relations in the secondary school context, but emphasised how the socially contingent nature of pupil's own understandings of religious identity could also contribute to a cohesive school community. Schools cannot be viewed in isolation from their local neighbourhoods and a number of studies, including those by Ipgrave (2012) and Holden (2009) have highlighted the importance of locality and region for understanding pupil attitudes towards religion and religious difference.…”
Section: Belongingmentioning
confidence: 99%